Assessment of the impact of the new blister packaging of Biktarvy® (B/F/TAF) on treatment satisfaction of people living with HIV - João Paulo Cruz; Osvaldo Santos; Marisa Rodrigues; Raquel Morais; Teresa Borralho; Filipa Ferreira; Abigail Ferreira; João Albuquerque; Paulo Nogueira; Maria Pinto da Silva; Francisco Antunes (PLoS ONE, 2025)
Background Antiretroviral therapy (ART) is highly effective in people living with HIV (PLHIV), but its success depends on treatment satisfaction and adherence. A determinant of satisfaction regards how the medication is delivered to the patient, namely how it is contained (e.g., bottles, blisters, etc). A new packaging of Biktarvy ® has been introduced as a monthly blister, aiming to improve satisfaction, facilitate traceability of daily medication, portability, and discretion (reducing stigma associated with ART), and, ultimately, enhance adherence. Goals The study’s objective was to assess the impact of changing the packaging of Biktarvy® (B/F/TAF) from a standard pill bottle to a monthly blister with a weekly calendar on therapy satisfaction. Additionally, the association between treatment satisfaction and selected patients’ characteristics (e.g., ART duration) was evaluated. A secondary goal was to characterize the association between the change of packaging on patient’s adherence. Methods This is an observational longitudinal (retrospective and prospective) study with patients following ART for at least six months (ambulatory clinical management) recruited according to a non-probabilistic sequential sampling. Satisfaction was measured at two different moments: at baseline, HIVTSQs were used to assess satisfaction within the previous six months’ use of medication containers (bottles). Six months later, patients filled in the HIVTSQc to assess their perception of satisfaction change with the new packaging (blister). Adherence was assessed by pharmacy medication dispensing at the hospital. Results The study enrolled 105 patients in two selected centers (102 patients completed the study). Patients were significantly more satisfied (HIVTSQc scores) with ART when using the new Biktarvy® blister pack package. Importantly, gains of ART satisfaction were higher among those less satisfied with the bottle packaging. No significant associations were found between HIVTSQc scores and sociodemographic or ART-related variables.